2017
DOI: 10.1080/14647273.2017.1388545
|View full text |Cite
|
Sign up to set email alerts
|

The association of renin–angiotensinogen system genes polymorphisms and idiopathic recurrent pregnancy loss

Abstract: The most common complication of pregnancy is idiopathic recurrent pregnancy loss (RPL). To identify the contribution of gene polymorphisms to this condition, we evaluated the association between RPL and the angiotensinogen (AGT), angiotensin receptor 1 (AGTR1) and Angiotensinogen converting enzyme (ACE). In this case-control study, the frequency of AGT (rs4762 and rs699), AGTR1 (rs5186) and ACE insertion/deletion (rs4340) polymorphisms in 202 idiopathic RPL women was compared with 210 women with no history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Subsequently, 75 publications were excluded because they were reviews, previous meta-analyses, and evaluated the association of RPL with other polymorphism of ACE and PAI-1 genes. Finally, a total of 14 studies involving eight studies with 783 patients and 761 controls on the ACE I/D polymorphism ( 6 , 18 , 29 , 32 , 33 , 34 , 35 ) and six studies with 1155 patients and 699 controls on the PAI-1 4G/5G polymorphism ( 18 , 31 , 34 , 36 38 ) were included in this meta-analysis. One study in the present meta-analysis did not state the source of controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, 75 publications were excluded because they were reviews, previous meta-analyses, and evaluated the association of RPL with other polymorphism of ACE and PAI-1 genes. Finally, a total of 14 studies involving eight studies with 783 patients and 761 controls on the ACE I/D polymorphism ( 6 , 18 , 29 , 32 , 33 , 34 , 35 ) and six studies with 1155 patients and 699 controls on the PAI-1 4G/5G polymorphism ( 18 , 31 , 34 , 36 38 ) were included in this meta-analysis. One study in the present meta-analysis did not state the source of controls.…”
Section: Resultsmentioning
confidence: 99%
“…The etiology of RPL is complicated, and several risk factors are involved in the development of the disease. In addition to fetal and maternal factors, including chromosomal abnormalities, endocrine and metabolic aberrations, and autoimmune abnormalities, genetic single nucleotide polymorphisms at different loci, also play essential roles in RPL ( 6 , 12 , 39 ) . In this meta-analysis, we evaluated the association of the ACE I/D and PAI-1 4G/5G polymorphisms with RPL risk in Iranian women from all eligible case-control studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data by several regions demonstrated that the D allele and DD genotype leads to a high PAI-1 level which reduced fibrinolysis and thus correlated with an increased risk of IRPL [9,12,15]. Many studies have been managed to explore the link between ACE I/D polymorphism alleles and genotypes and IRPL, but the results of these studies differ from each other [13][14][15][19][20][21][22][23][24]. Our results showed that the ACE I/D polymorphism was associated with IRPL, and that women that carried DD or ID genotypes had a 72% elevated risk of developing IRPL than women with the II genotype [OR (95% CI): 1.72 (1.181-2.5)].…”
Section: Discussionmentioning
confidence: 99%
“…Several researches were also conducted to search the possible association with ACE I/D polymorphism and IRPL. The potential role of ACE I/D polymorphism in IRPL pathogenesis has been controversial [3,9,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%